Can visual cortex non-invasive brain stimulation improve normal visual function? A systematic review and meta-analysis - Bello, Umar M.; Wang, Jingying; Park, Adela S. Y.; Tan, Ken W. S.; Cheung, Blossom W. S.; Thompson, Benjamin; Cheong, Allen M. Y. (Frontiers in Neuroscience, 2023)
Objective: Multiple studies have explored the use of non-invasive brain stimulation (NIBS) to enhance visual function. These studies vary in sample size, outcome measures, and NIBS methodology. We conducted a systematic review and meta-analyses to assess the effects of NIBS on visual functions in human participants with normal vision. Methods: We followed the PRISMA guidelines, and a review protocol was registered with PROSPERO before study commencement (CRD42021255882). We searched Embase, Medline, PsychInfo, PubMed, OpenGrey and Web of Science using relevant keywords. The search covered the period from 1st January 2000 until 1st September 2021. Comprehensive meta-analysis (CMA) software was used for quantitative analysis. Results: Forty-nine studies were included, of which 19 were included in a meta-analysis (38.8%). Meta-analysis indicated acute (Hedges’s g=0.232, 95% CI: 0.023-0.442, p=0.029) and aftereffects (0.590, 95% CI: 0.182-0.998, p=0.005) of transcranial electrical stimulation (tES, including three different stimulation protocols) on contrast sensitivity. Visual evoked potential (VEP) amplitudes were significantly enhanced immediately after tES (0.383, 95% CI: 0.110-0.665, p=0.006). Both tES (0.563, 95% CI: 0.230 to 0.896, p=0.001)] and anodal-transcranial direct current stimulation (a-tDCS) alone (0.655, 95% CI: 0.273 to 1.038, p=0.001) reduced crowding in peripheral vision. The effects of NIBS on visual acuity, motion perception and reaction time were not statistically significant. Conclusions: There are significant effects of visual cortex NIBS on contrast sensitivity, VEP amplitude, an index of cortical excitability, and crowding among normally sighted individuals. Future studies with robust experimental designs are needed to substantiate these findings in populations with vision loss.